The Educational Values in Fairy Tale Cartoon Film - Erlidawati, Erlidawati; Rahmah, Siti (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
The educational value is the value that can form someone’s attitude to be a good person. This value is given by teachers, parents, and others that contain education, morals and manners have a good value in it. Educational value can also be taken from literary works such as films, poetry, novels, stories of fairy tale and so on. One of literary works that can give the knowledge for educational value is fairy tale cartoon film, which telling children’s story about magical and imaginary beings and lands. There were many educational values that could be taken as a lesson in human’s life from fairy tale. This could be taken from fairy tale are moral value, social value, family value. It could be concluded that a good film will give a good impact for everyone has watched the film. The educational value from that film not only for enjoying but also it can be applied in our daily life activities.